PERUBAHAN IDEOLOGI KEISLAMAN TURKI (Analisis Geo-Kultur Islam dan Politik Pada Kerajaan Turki Usmani) - Tabrani ZA (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2016)
The emergence of Islam in world history storing a number of unique and magic. And the contribution of Islam in the world also has long received the recognition. Since centuries, the spread of Islam in various parts of the world has an impact to human life in the political system, social, economic, and cultural. Turkey geographic position located him between two different continents, namely Asia and Europe, is a unique strategic position at the same time. The spirit of modern Turkish society to become a modern and democratic nation, always accompanied by a profound awareness of the character and ideals to Turkishness and to Islamization. The author notes that the idea of a synthesis of Islam, Turkey and the West ever raised by Ziya Gokalp (Mr. nationalist Turkey) began to be implemented with a reasonable and natural, while the state ideology of Kemalism made its presence very well guarded by the Turkish military forces. There are three areas that can be observed in the impulse secularists who is the most prominent element of the Kemalist reforms. First, is the secularization of the state, education, and law, in the form of attacks against traditional powerhouses scholars institutionalized. Secondly, it is an attack against the symbols of European civilization. Third, is the secularization of social life and an attack against Islam embraced people.